2019
DOI: 10.1111/rode.12626
|View full text |Cite
|
Sign up to set email alerts
|

Informality, innovation, and aggregate productivity growth

Abstract: This paper investigates how the ability to innovate affects firms' decisions to operate informally and the aggregate consequences of their sectoral choice. I embed a sectoral choice model, where firms choose to operate in the formal or informal economy, into a richer general equilibrium environment to analyze the aggregate effects of firm-level decisions in response to government taxation. I calibrate the model and conduct simulations to quantify the impacts on the aggregate economy. I find that a change in ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…On the other side, the viability of informal businesses may depend on their capacity for innovation. Schipper (2014) integrates a sectoral choice model in which firms operate in the formal or informal economy into a more robust general equilibrium framework to examine the aggregate effects of firm-level activities in response to government taxation. In contrast, the informal sector has occasionally been a source of innovations, and formal and informal enterprises have collaborated on introducing innovations in some instances (George et al, 2012).…”
Section: Firm's Resource Characteristics and Formalitymentioning
confidence: 99%
“…On the other side, the viability of informal businesses may depend on their capacity for innovation. Schipper (2014) integrates a sectoral choice model in which firms operate in the formal or informal economy into a more robust general equilibrium framework to examine the aggregate effects of firm-level activities in response to government taxation. In contrast, the informal sector has occasionally been a source of innovations, and formal and informal enterprises have collaborated on introducing innovations in some instances (George et al, 2012).…”
Section: Firm's Resource Characteristics and Formalitymentioning
confidence: 99%
“…This finding is supported by recent empirical evidence which shows that the survival of informal firms is linked to their ability to be innovative (Fu et al 2015). In addition, research has shown that, for new entrants, innovation impacts on entrepreneurial decisions to operate informally or formally (Schipper 2020). Further, for firms in both the informal and formal sectors, innovation is important for cost efficiency, competitiveness, and growth (McEvily et al 2004;Senge et al 2001).…”
Section: Entrepreneurship Trade and Business Densitymentioning
confidence: 99%
“…Such circumstances are likely to be associated with an environment of weak regulatory and tax enforcement(Quintin 2008;Ulyssea 2010;Benjamin and Mbaye 2012).3 This has been documented for some Latin America countries, India, Poland, Portugal, the Russian Federation, and Turkey. For evidence, seeHeredia et al (2017),Perry et al (2007),Farrell (2004),Capp et al (2005),Cunha (2006),Gonzlez and Lamanna (2007),Friesen and Wacker (2013),Allen and Schipper (2016),Iriyama, Kishore, and Talukda (2016),and Distinguin, Rugemintwari, and Tacneng (2016).4 This has been documented for the Arab Republic of Egypt, seeAli and Najman (2017),Melitz (2003),and Schipper (2016).…”
mentioning
confidence: 97%